From Dictatorship of the Proletariat to Personnel (why the Hegemon didn’t become the Leader of Progress) - Valentina Prokofyevna Vershel (Управленческое консультирование)
Today there is a set of the points of view on destiny of working class. One still consider working class as «the history engine», «the leader of progress» and isolated facts of a working protest treat as manifestation of a powerful role of working class. Others note transformation of workers from a class in the professional group, which is poorly defending the not class, but professional interests. The third urge to return back, to dictatorship of the proletariat. Where there is a working class today?